Vergleichende Periglazialmorphologie im Sommerregengebiet der Atacama - Schröder, Hilmar (ERDKUNDE, 1999)
The periglacial processes in the summer rainfall area in the High Andes of Chile between Parinacota 18°10’S and Llullaillaco 24°43’S and resulting periglacial phenomena are presented here. The landforming processes reflect the extremely arid recent and present climate. The range of periglacial landforms, the vertical distribution and association of which is described here, results from the interactions of climate and bedrocks. The upper periglacial limits are the highest of the world. Due to the extreme aridity, glaciers to the south of 21°12’S and rock glaciers to the south of 21°32’S cannot form today. Therefore, their absence is not due to insufficiently low temperatures, but to lack of humidity.